Flexible photovoltaic generation strategy for Rome Technopole - Gianluigi Bovesecchi; Federico Andreozzi; Marcello Petitta; Marco Pierro; Richard Perez; Cristina Cornaro (Energy Conversion and Management: X)
As part of Italy’s National Recovery and Resilience Plan (PNRR), the “Rome Technopole” innovation ecosystem focuses on Energy Transition. Within this initiative, the RES4TECH project aims to meet the electricity demand of the future Rome Technopole campus through energy-flexible photovoltaic (PV) systems with battery energy storage systems (BESS).These energy-flexible PV systems with BESS, integrated with smart inverters and remote control, are designed to deliver power reliably under two scenarios: one delivering forecasted generation, and the other matching a continuous demand profile (24/365 firm generation). Since the Rome Technopole will be completed by 2030, the expected electrical load was modeled using data from the Engineering Macro-area at the University of Rome Tor Vergata (2013–2021). Solar and climate data from the university’s EsterLab enabled simulations of PV generation at various tilt angles, identifying 30° south-facing as optimal.An optimization process was developed to determine the ideal balance between PV and BESS capacity to minimize energy costs. Simulations show that oversizing PV capacity (3.9 times the annual electrical demand) and integrating storage can fully cover electricity needs. The optimal system includes 9.5 MWp of PV and 16.8 MWh of storage to serve an average daily demand of 9.84 MWh.A financial analysis indicates that 65 % self-production is already cost-effective today (LCOE = 112 €/MWh, payback period = 11 years). Achieving 80 % self-generation would currently require 28 years, but this could drop to 9 years if 2050 technology costs are reached by 2030.